Internalization of Ethical and Moral Values in Shaping Student Character at a Higher Education Institution (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to identify and analyze violations of the academic code of ethics in higher education institutions, including plagiarism, data manipulation, and verbal abuse, as well as their causes and implications. Employing a qualitative research method, data were collected through in-depth interviews, observations, and documentation from various informants within the academic community. The findings indicate that low understanding of academic ethics, academic pressure, and weak supervisory systems are the primary factors contributing to violations. The study recommends strengthening academic literacy, implementing transparent reporting mechanisms, and fostering an academic culture rooted in integrity as strategic measures to address these issues. This research contributes to the development of higher education policies focused on enhancing academic integrity.